Lasers and optoelectronics : fundamentals, devices, and applications - Maini, Anil Kumar (Chichester, West Sussex, United Kingdom : John Wiley & Sons Inc., 2013)
With emphasis on the physical and engineering principles, this book provides a comprehensive and highly accessible treatment of modern lasers and optoelectronics. Divided into four parts, it explains laser fundamentals, types of lasers, laser electronics & optoelectronics, and laser applications, covering each of the topics in their entirety, from basic fundamentals to advanced concepts. Key features include: exploration of technological and application-related aspects of lasers and optoelectronics, detailing both existing and emerging applications in industry, medical diag.
Laser basics -- Laser characteristics -- Types of lasers -- Types of lasers (gas lasers) -- Types of lasers (semiconductor lasers) -- Building blocks of laser electronics -- Solid state laser electronics -- Gas laser electronics -- Laser diode electronics -- Optoelectronic devices and circuits -- Lasers in industry -- Lasers in medicine -- Lasers in science and technology -- Military applications -- Military applications (directed energy laser systems).
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Lasers; Optoelectronic devices; Lasers; Microwaves; Optoelectronic devices; Optoelectronics; TECHNOLOGY & ENGINEERING -- Mechanical; Lasers; Optoelectronic devices; Electronic books; Electronic books